DRILL Interface Makes Ion Soft Landing Broadly Accessible for Energy Science and Applications. Issue 3 (22nd June 2018) - Johnson, Grant E.; Prabhakaran, Venkateshkumar; Browning, Nigel D.; Mehdi, B. Layla; Laskin, Julia; Kottke, Peter A.; Fedorov, Andrei G.
Abstract: Polyoxometalates (POM) have been deposited onto carbon nanotube (CNT) electrodes using benchtop ion soft landing (SL) enabled by a vortex‐confined electrohydrodynamic desolvation process. The device is based on the dry ion localization and locomotion (DRILL) mass spectrometry interface of Fedorov and co‐workers. By adding electrospray emitters, heating the desolvation gas, and operating at high gas flow rates, it is possible to obtain stable ion currents up to −15 nA that are ideal for deposition. Coupled with ambient ion optics, this interface enables desolvated ions to be delivered to surfaces while excluding solvent and counterions. Electron microscopy of surfaces prepared using the device reveal discrete POM and no aggregation that degrades electrode performance. Characterization of POM‐coated CNT electrodes in a supercapacitor showed an energy storage capacity similar to that achieved with SL in vacuum. For solutions that produce primarily a single ion by electrospray ionization, benchtop SL offers a simpler and less costly approach for surface modification with applications in catalysis, energy storage, and beyond. Abstract : Soft landing without vacuum : An interface is developed that enables controlled deposition of ions onto surfaces at benchtop conditions. The device separates ions from solvent as well as counterions, allowing discrete ions to be immobilized on electrodes which exhibit similar performance to those prepared with vacuum‐based ion soft landing. The simplicity and lower cost of this approach make ion soft landing accessible to the scientific community.